Pengaruh Massage Effleurage Terhadap Penurunan Skala Nyeri Afterpain Pada Ibu Postpartum Multipara - Syahriana, Syahriana; Jasmawati, Jasmawati; Raihanah, Siti (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Afterpain is the feeling of cramps, heartburn that is felt by the mother after giving birth. An effective pain management strategy involves both pharmacological and non-pharmacological methods for reducing pain. Non-pharmacological therapies include the effleurage massage technique. It was determined that massage effleurage reduced the afterpain pain scale among multiparous postpartum women at Abdoel Wahab Sjahranie Hospital. Method research involves a quasi-experimental design with two groups, a pretest and a posttest, as well as a control group design. Population is all multiparous postpartum at Abdoel Wahab Sjahranie Hospital. The samples are 18 peoples for each group. Total sample are 36 peoples with purposive sampling technique. The independent variable is massage effleurage and the dependent variable is the pain scale. The statistical tests used by Wilcoxon test and Mann Withney test. There is an effect of massage effleurage on decreasing afterpain scale in multiparous postpartum at Abdoel Wahab Sjahranie Hospital with a significance value pvalue 0,000 less than 0,05 (p less than α). Massage effleurage is effective in reducing postpartum pain in multiparous women. Health workers can apply pain management in the form of effleurage massage techniques according to the procedure for postpartum mothers. Families can apply this technique independently. Meanwhile, other researchers can conduct research with different variables.